PERAN HADIS DALAM MENDIDIK AKAL DAN MEMBANGUN KARAKTER SISWA - Mumu Munawar; Yuki Zaki Mubarok; Anindya Rizka Ayunda; Fhirda Faiza; Maslani Maslani (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
Hadith as the main source of Islamic teachings has an important role in educating the mind and building human character. In Islam, reason is seen as a gift that must be educated to be able to think critically, rationally, and based on religious values, while character includes the formation of noble morals that become the basis of human behavior. This study aims to analyze the role of hadith in the education of reason and character building and its relevance in modern life. The research method used is qualitative with a descriptive-analytical approach through a literature study, which involves an in-depth study of the traditions related to the education of reason and character building. The results show that the Prophet's hadith provides comprehensive direction in educating the intellect through the recommendation to study and think critically, as well as building character through the internalization of moral values such as honesty, patience, and compassion. This synergy between intellect and character education not only forms intelligent and moral individuals, but also supports the creation of a harmonious and civilized society. This study emphasizes the importance of integrating the teachings of hadith in the education system to create a complete human being in accordance with the goals of Islamic education.